Multi-Level Adaptive Video Streaming Over Wireless Channels - Mukhtar, Husameldin (2010)
A Master of Science Thesis in Electrical Engineering Submitted by Husameldin Mukhtar Entitled, "Multi-Level Adaptive Video Streaming Over Wireless Channels," May 2010. Available are both Soft and Hard Copies of the Thesis